Autonomous Vehicles from another Perspective – A Literature Analysis - László Berek (Interdisciplinary Description of Complex Systems, 2023)
Autonomous vehicles are part of our everyday lives, but with the rapid development of technology, this will become more and more common. Research on self-driving cars will replace conventional vehicles not only in passenger transport but also in the transport of goods and industrial materials. Car companies and research institutes are conducting more and more research in the face of serious economic interests. This study analyses published papers on self-driving vehicles and their security issues. A more detailed analysis of the publication output of the last six years is also included. The analysis of the publications by country shows that the Asian region has invested considerable efforts in the research and development of self-driving cars and their safety issues in the last three years.